1977
DOI: 10.1098/rspa.1977.0171
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of entropy fluctuations with turbine blade rows; a mechanism of turbojet engine noise

Abstract: The theory relating to the interaction of entropy fluctuations (' hot spots '), as well as vorticity and pressure, with blade rows is described. A basic feature of the model is that the blade rows have blades of sufficiently short chord that this is negligible in comparison with the wavelength of the disturbances. For the interaction of entropy with a blade row to be important, it is essential that the steady pressure change across the blade row should be large, although all unsteady perturbations are assumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 4 publications
1
85
0
Order By: Relevance
“…There exist several methods to solve this system of equations. Here, a modification of the method proposed by Cumpsty & Marble (1977) to solve the propagation of acoustic and entropy waves through a two-dimensional compact stator vane is adapted to the one-dimensional non-compact nozzle. The matrix system of equation (5.4) can be rearranged to have the unknowns on one side of the equation and the forcing values of the waves on the other side.…”
Section: Subsonic Flowmentioning
confidence: 99%
“…There exist several methods to solve this system of equations. Here, a modification of the method proposed by Cumpsty & Marble (1977) to solve the propagation of acoustic and entropy waves through a two-dimensional compact stator vane is adapted to the one-dimensional non-compact nozzle. The matrix system of equation (5.4) can be rearranged to have the unknowns on one side of the equation and the forcing values of the waves on the other side.…”
Section: Subsonic Flowmentioning
confidence: 99%
“…It has been demonstrated that unsteady flames can generate entropy waves, which are advected downstream by the mean flow and may reach the exit nozzle of the combustor [3,5,6]. Due to the significant acceleration of the mean flow in the exit nozzle and the first stages of the high pressure turbine, entropy waves can be converted into acoustic waves [7,8]. This forms a source of noise in the gas turbine, which originates from the combustion process.…”
Section: Introductionmentioning
confidence: 99%
“…The compact approximation works well when the nozzle is much shorter than all the wavelengths. The compact nozzle theory of Marble & Candel [6] was extended by Cumpsty & Marble [19,20] and Cumpsty [21] to study entropy noise produced in a gas turbine at the combustor outlet and turbine blade stages. A significant increase of entropy noise generation was found with the increase of pressure drop over a turbine stage.…”
Section: Introductionmentioning
confidence: 99%